Exploring the diets of mothers and their partners during pregnancy: Findings from the Queensland Family Cohort pilot study. Issue 5 (30th March 2022) - Wilkinson, Shelley A.; Schoenaker, Danielle A. J. M.; de Jersey, Susan; Collins, Clare E.; Gallo, Linda; Rollo, Megan; Borg, Danielle; Dekker Nitert, Marloes; Truby, Helen; Barrett, Helen L.; Kumar, Sailesh; Clifton, Vicki
Abstract: Aim: Modifiable behaviours during the first 1000 days of life influence developmental trajectories of adult chronic diseases. Despite this, sub‐optimal dietary intakes during pregnancy and excessive gestational weight gain are common. Very little is known about partners' dietary patterns and the influence on women's pregnancy dietary patterns. We aimed to examine dietary intake during pregnancy among women and their partners, and gestational weight gain patterns in the Queensland Family Cohort pilot study. Methods: The Queensland Family Cohort is a prospective, observational study piloted at a Brisbane (Australia) tertiary maternity hospital from 2018 to 2021. Participant characteristics, weight gain, dietary and nutrient intake were assessed. Results: Data were available for 194 pregnant women and their partners. Poor alignment with Australian Guide to Healthy Eating recommendations was observed. Highest alignment was for fruit (40% women) and meat/alternatives (38% partners) and lowest for breads/cereals (<1% women) and milk/alternatives (13% partners). Fewer women (4.4%–60.3%) than their partners (5.4%–92.3%) met guidelines for all micronutrient intakes from food alone, particularly folic acid, iodine, and iron. Women were more likely to meet daily recommendations for fruit, vegetables, dairy, bread/cereals, and meat/alternatives when their partners also met recommendations. Women with a higher pre‐pregnancy body mass index were more likely to gain above recommended weight gain ranges. Conclusions: In this contemporary cohort of pregnant women and their partners, sub‐optimal dietary patterns and deficits in some nutrients were common. There is an urgent need for evidence‐informed public health policy and programs to improve diet quality during pregnancy due to intergenerational effects.